EFL Students’ Perceptions on the Use of Promova for Learning English Vocabulary - Jannah, Miftahul; Daulay , Ernita (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study explores EFL students' perceptions of using the Promova application to learn English vocabulary. The study employed a qualitative descriptive method with 30 XIth-grade students at a senior high school in Medan. Data were collected through Likert scale questionnaires and semi-structured interviews. The results indicate that students perceive Promova as a user-friendly, flexible, self-directed learning application. Interactive features, such as quizzes, flashcards, image illustrations, and AI-based pronunciation feedback, increase vocabulary memorization, enhance understanding, and boost learning motivation. While most students feel confident and enjoy learning with Promova, some remain neutral about its impact on long-term motivation. These findings suggest that Promova is an effective vocabulary-learning tool for EFL students. This study implies that mobile applications like Promova can be used as an engaging and tailored language learning media. This study contributes to the literature review by offering an understanding of students' experiences using the Promova application in Indonesian secondary schools, a topic rarely discussed in previous studies. Additionally, the results can be a useful reference for teachers, application developers, and future researchers when designing vocabulary learning media suited to students' needs and interests.